PANCASILA SEBAGAI SOLUSI PLURALISME DI INDONESIA - RICKY BANKE; STEVEN STEVEN; NICHOLAS SUSANTO (JURNAL ILMIAH MAKSITEK, 2023)
Pluralism has become one of the characteristics of the Indonesian nation with its diversity in culture, ethnicity, beliefs, etc. Indonesia's plural cultural structure if not managed properly can be a challenge as well as a threat of conflict. Therefore, a solution is needed as a common agreement, namely Pancasila, which must be a reference in establishing unity and resolving / eliminating potential. Pancasila can be the main foundation for running the life of the nation and state in the face of plurality. Each precept of Pancasila is elaborated in relation to pluralism and other principles. Godhead, humanity, Indonesian unity, democracy, and justice are very important precepts to foster the spirit of communication, mutual understanding and cooperation among various plural groups with an approach based on Pancasila values. Pluralism in Indonesia can be a useful asset that encourages progress and social harmony. Pancasila education has a vital function in building citizens' awareness to adopt Pancasila values as a solution to overcome the obstacles of pluralism and turn it into a force for the prosperity and welfare of the nation.